Narasi mahasiswa tentang pendidikan anti korupsi berbasis Pancasila: Analisis kualitatif tentang kesadaran moral dan perilaku - Azizah, Nur Alfi (Maliki Interdisciplinary Journal, 2025)
This study aims to deeply understand how students make meaning of and experience anti-corruption education based on Pancasila values, and how these experiences influence their moral awareness and behavior. Using a qualitative approach and narrative analysis method, this research explores the stories, experiences, and reflections of students related to anti-corruption education. Data were collected through in-depth interviews with students from various academic backgrounds and student organizations who have participated in anti-corruption education programs based on Pancasila. Data analysis was conducted by identifying key themes that emerged from the students' narratives, such as understanding of corruption, internalization of Pancasila values, changes in perceptions of morality, and strategies for dealing with ethical dilemmas. The results of the study indicate that anti-corruption education based on Pancasila not only provides knowledge about the dangers of corruption but also helps students develop a deeper moral awareness and a commitment to act honestly and with integrity. Furthermore, this study also found that students' narratives reflect a complex meaning-construction process, in which they integrate Pancasila values with their personal experiences and social contexts. Anti-corruption education also plays a role in shaping students' moral identity as agents of change who have a responsibility to eradicate corruption. The implication of this research is the importance of developing anti-corruption education programs that not only focus on cognitive aspects but also on affective and behavioral aspects, as well as the need to actively involve students in the learning process. This study contributes to a more comprehensive understanding of how anti-corruption education can shape students' character to be integrity-driven and committed to Pancasila values.